2022
DOI: 10.1093/bjs/znac074
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative interventions to reduce pancreatic fistula following pancreatoduodenectomy: meta-analysis

Abstract: Background Data on interventions to reduce postoperative pancreatic fistula (POPF) following pancreatoduodenectomy (PD) are conflicting. The aim of this study was to assimilate data from RCTs. Methods MEDLINE and Embase databases were searched systematically for RCTs evaluating interventions to reduce all grades of POPF or clinically relevant (CR) POPF after PD. Meta-analysis was undertaken for interventions investigated in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Although each procedure has some advantages and disadvantages, several systematic reviews and meta-analyses failed to show the superiority of either technique [17][18][19]. In the Pancreatic Anastomosis Audit (PARANOIA) study, the authors reported that invagination PJ, compared to the duct-to-mucosa technique, was associated with reduced rates of all POPF, including biochemical leaks and clinically relevant fistula types [17]. The most recent version of the Cochrane review did not find any significant difference between duct-to-mucosa and invagination PJs in terms of the development of Grade B or C POPFs [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although each procedure has some advantages and disadvantages, several systematic reviews and meta-analyses failed to show the superiority of either technique [17][18][19]. In the Pancreatic Anastomosis Audit (PARANOIA) study, the authors reported that invagination PJ, compared to the duct-to-mucosa technique, was associated with reduced rates of all POPF, including biochemical leaks and clinically relevant fistula types [17]. The most recent version of the Cochrane review did not find any significant difference between duct-to-mucosa and invagination PJs in terms of the development of Grade B or C POPFs [18].…”
Section: Discussionmentioning
confidence: 99%
“…One aspect of this is the lack of an accepted 'standardised practice', which means that designing an appropriate control group to minimise the impact of important confounders is challenging. Additionally, pancreatic surgery trials typically struggle with timely recruitment and therefore are frequently underpowered to detect meaningful differences [117]. Clear, standardised outcomes to evaluate the effect of nutritional therapies have also been lacking, making designing and powering clinical trials extremely difficult.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…As such, they have been investigated as part of singular and combination strategies for reducing CR-POPF. Ulinastatin, a trypsin inhibitor, has been found to significantly reduce CR-POPF after PD in a meta-analysis combining two studies (Table 5) [30]. Its mechanism of inactivating pancreatic juice may also explain the noted reduction in PPAP after PD [134].…”
Section: Protease Inhibitorsmentioning
confidence: 99%